Phytolith production-weighed meteorological averages from West Africa (Benin and Senegal) - Alexandre, Anne (In: Alexandre, A (2025): Climate and triple oxygen isotope of precipitation, groundwater, soil water, plant water, and phytolith data from West Africa (Benin and Senegal) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984133, 2025)
Daily and daytime meteorological averages calculated for the sampled years and rainy seasons at Belefoungou (BE, Benin, Nalohou (NA, Benin) and Dahra (DA, Senegal) from 2018 to 2021.
Keywords: phytolith; plant water; precipitation; soil water; triple oxygen isotopes; West Africa